Political Behaviours of Internal Auditors in the Indonesian Public Organisation - Muhammad Syaebani; Annisa Merdekawati; Monica Devina; Dindha Primadini (Program Studi S3 Ilmu Manajemen, 2021)
Political behaviours are common in a workplace, including in a public organisation. However, political behaviours are like a double-edged sword. They could support the management, but on the other hand, they could also turn into a negative side which generates some drawbacks and inhibits the effectiveness of management. This research focuses on types, causes, impacts, and solutions of internal auditors’ political behaviours. We used the phenomenological methodology and qualitative approach. Interviews were conducted with ten auditors from various backgrounds to ensure the validity of the findings. This research revealed four main conclusions. First, there are two types of political behaviour, namely defensive political behaviour and impressive management. Second, the causes of political behaviour are individual and organisational. Third, the political behaviour could impact intrapersonal auditors, interpersonal relationship, and organisation as a whole. Fourth, this research indicates solutions to encounter the problems by improving the human resource system and organisational culture.